Contenidos Teóricos Y Ejercicios Prácticos Para El Baile Del Joropo Tradicional O Criollo, Una Mirada Previa De La Asignatura Danza Llanera, En La Licenciatura De Educación Artística Danza Y Teatro De La Uan (2017)
The importance of the llanera culture will only be understood through history, which is why, Within the information collection process, different theoretical aspects are revealed. that contribute to the development of this work, information is obtained from different theoretical sources such as Casadiegos and Abadia, who with their contributions make the history of joropo and tradition llanera is more easily understood. However, the most important thing about this work is the data corresponding to the Danza Llanera where each of its main elements is contained for the execution (steps, figures, costumes and instruments), characterizing each of these and contributing to the knowledge of students within the Bachelor's Degree in Art Education with Emphasis in Dance and Theater from the Antonio Nariño University.